The figurative language: Metaphor and personification in the poetry of William Shakespeare and William Blake - Anjani, Silvia Putri; Darmawan, Radik (Yayasan Mitra Persada Nusantara, 2024)
The author in making this journal aims to provide more understanding and information for many people, so that it can be used for their further research or become reference material for their assignments. In making it, the author chooses a qualitative method because it can get a lot of information presented in words or explanatory sentences. The topic taken in journal writing is about metaphor and personification in the poems of William Shakespeare and William Blake. The poems taken by the researcher are four titles namely ‘Sonnet 16’, Sonnet 18 (Shall I Compare Thee to Summer's Day?’, “The Tyger”, and “London”. This research produces the same number of metaphors and personification, 11, with William Shakespeare's poems using the least metaphors and personification compared to William Blake's poems. So, in this research the author can provide a lot of new information to be used in activities or tasks carried out in education, to add information as a complement to previous journals.